GÜRÜLTÜ OLGUSU VE GÜRÜLTÜNÜN ÖNLENMESİ KAPSAMINDA GÜRÜLTÜ VERGİSİNE YÖNELİK KAVRAMSAL BAKIŞ - Ufuk GERGERGLİOĞLU (International Journal of Eurasia Social Sciences, 2017)
It is known that noise is a sound level which discomforts the human ear. Especially in today’s modern life, the dimension of noise has expanded considerably. The phenomenon of noise which is described as an environmental problem has forced the governments of some countries to take measures in this regard. One of these measures is noise taxes. The reason for the implementation of this tax is the elimination of the externalities which take place because of the noise. When examining the implementations of this tax in some countries, it seems that this tax is especially implemented in air transport. In this study, it is aimed that noise tax is explained in the context of the countries’ applications by addressing to the concept of noise in detail. Up to now, noise taxes have been examined from a narrow perspective within the context of environmental taxes in Turkey. This has created more motivation for this work to be presented.